The origins of secular institutions: ideas, timing, and organization - Bulutgil, Zeynep (Oxford University Press USA - OSO, 2022)
In The Origins of Secular Institutions, H. Zeynep Bulutgil studies why some countries adopt secular institutions while others do not. Her main finding is that the timing of secular ideas and the organizational strength of secular political groups played a key role in the adoption of secular institutions. Based on cross-national statistical evidence since 1800 and in-depth analysis of selected cases in Europe and the Middle East/North Africa, the book explores how secular ideas emerged and spread, whether and how they culminated in political organizations, and the conditions under which such organizations succeeded in establishing secular institutions.